Gross Morphological and Morphometrical Studies on the Metacarpals of Blue Bull (Boselaphus tragocamelus) - Bharti, Sanjay Kumar (Indian Journal of Veterinary Anatomy, 2020)
The present study was conducted on the metacarpals of six adult blue bull of either sex collected from Jodhpur zoo, Rajasthan, after obtained official permission. The metacarpus of blue bull consisted of two metacarpal bones. The large metacarpal bone consisted of fused III and IV metacarpals. The shaft was compressed from side to side and presented two surfaces and two borders. The anterior surface was smooth and rounded in outline side to side and presented proximal and distal foremen. The palmar surface was flat in outline and it presented a deep longitudinal groove that possessed similar foramina. These foramina communicated with the similar foramina on the palmar surface through transverse canals. The proximal extremity presented two slightly concave facets, separated by a median ridge in front and a shallow groove behind. The distal extremity was divided by a dorsopalmar cleft into two condyles. The small metacarpal V was rounded with distally pointed end in blue bull.